FGFR4 signaling couples to Bim and not Bmf to discriminate subsets of alveolar rhabdomyosarcoma cells. Issue 7 (3rd March 2014) - Wachtel, Marco; Rakic, Jelena; Okoniewski, Michal; Bode, Peter; Niggli, Felix; Schäfer, Beat W.
Abstract : Biological heterogeneity represents a major obstacle for cancer treatment. Therefore, characterization of treatment‐relevant tumor heterogeneity is necessary to develop more effective therapies in the future. Here, we uncovered population heterogeneity among PAX/FOXO1‐positive alveolar rhabdomyosarcoma by characterizing prosurvival networks initiated by FGFR4 signaling. We found that FGFR4 signaling rescues only subgroups of alveolar rhabdomyosarcoma cells from apoptosis induced by compounds targeting the IGF1R‐PI3K‐mTOR pathway. Differences in both proapoptotic machinery and FGFR4‐activated signaling are involved in the different behavior of the phenotypes. Proapoptotic stress induced by the kinase inhibitors is sensed by Bim/Bad in rescue cells and by Bmf in nonrescue cells. Anti‐apoptotic ERK1/2 signaling downstream of FGFR4 is long‐lasting in rescue and short‐termed in most non‐rescue cells. Gene expression analysis detected signatures specific for these two groups also in biopsy samples. The different cell phenotypes are present in different ratios in alveolar rhabdomyosarcoma tumors and can be identified by AP2β expression levels. Hence, inhibiting FGFR signaling might represent an important strategy to enhance efficacy of current RMS treatments. Abstract : What's new? The FGFR4 gene appears to play an important role in many cancers, including rhabdomyosarcoma (RMS). In this study, the authors treated a panel of RMS cell lines with compounds that trigger apoptosis. They found differences both in FGFR4‐activated signaling and pro‐apoptotic machinery between specific subsets of RMS cells. Gene‐expression analysis identified similar subsets in human tumor biopsies, indicating that the low success rate of current RMS therapies may involve tumor‐cell heterogeneity. Inhibiting FGFR signaling may thus be a useful strategy for enhancing the efficacy of these therapies.